The case of the perfect prank - Preller, James; Smith, Jamie C.; Alley, R. W. (Robert W.) (New York : Scholastic, 2004)
Jigsaw's brothers love to play practical jokes, but Jigsaw does not have time for games because Danika's kitty has been cat-napped and he is on the case.
"A Little Apple paperback."
2.0.
006-009.
480
Accelerated Reader AR
Keywords: Cats -- Juvenile fiction; Mystery fiction